EKONOMI POLITIK KEUANGAN SYARIAH DI INDONESIA - Aswad, Muhammad (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2015)
After experiencing a long process, the Indonesian government finally established the first syariah banking, named Bank Muamalah Indonesia (BMI) in 1993. The establishment of the first Islamic banking institution that is moementum rise of Islamic financial institutions in Indonesia. After that, sporadically emerging diverse Islamic financial institutions ranging from micro to macro. The society welcomed because Islamic financial institutions believed to be free of the riba. In addition, political influence can not be separated from the idea of an Islamic bank continuous public discourse by Moslem economists. Momentum birth of Islamic banking at the end of the New Order regime and the emergence of ICMI as a Moslem organization promotes the interests of Moslems in the national policy at the time. And equally important is the influence of Islam in the world economy global. Starting from Egypt, Pakistan, Malaysia, Bangladesh, Iran, Iraq, Jordan and Western countries such as Britain, France, and the USA.Keywords: Economy, Global Politic, Syariah